Prognostic value of T regulatory cells and immune checkpoints expression in tumor-draining lymph nodes for oral squamous cell carcinoma - Piersiala, Krzysztof; Hjalmarsson, Eric; Lagebro, Vilma; Farrajota Neves da Silva, Pedro; Bark, Rusana; Elliot, Alexandra; Marklund, Linda; Margolin, Gregori; Georén, Susanna Kumlien; Cardell, Lars-Olaf (Frontiers in Immunology, 2024)
Despite the employment of extensive therapeutic strategies, OSCC recurrence and mortality rates persist at high levels. This underscores the shortcomings of current prognostic models and the urgency for refined biomarkers. This study explores the prognostic significance of tumor-draining lymph nodes (TDLNs) in OSCC, with a special focus on the quantification of T regulatory cells (Tregs) and the expression of immune checkpoints on T cells. Methods Forty-nine OSCC patients were enrolled. One TDLN per patient was analysed using flow cytometry to profile immune-checkpoint expression (PD-1, CTLA-4, TIGIT, TIM-3, LAG-3) and other markers such as CD69, CXCR5 on CD4+, CD8+, and Tregs. Disease-free survival (DFS) and overall survival (OS) were assessed. Results According to multivariate analysis, elevated levels of FoxP3+CD4+ and TIGIT+CD8+ cells in TDLNs correlated with significantly worse DFS, while high CXCR5+CD4+ levels were associated with better DFS. Notably, the expression of immune checkpoints on T cells within TDLNs showed significant associations with recurrence status. Patients experiencing recurrence exhibited heightened levels of T regulatory cells, CD4+PD-1+ and CD4+CTLA-4+, cells in TDLNs. Survival multivariate analyses revealed that T status emerged as an independent predictor of OS. Conclusion The findings highlight the critical role of TDLNs in the immune microenvironment of OSCC and establish immune checkpoint expression on T cells as promising prognostic biomarkers. These insights upgrade the prognostic framework for OSCC and pave the way for individualized therapeutic strategies. The prognostic significance of TDLNs and a high expression of immune checkpoint inhibitors is a compelling argument for the adoption of neoadjuvant immunotherapy.